2017
DOI: 10.3892/mmr.2017.7329
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile-based screening of potential protein biomarkers in the urine of patients with nephrotic syndrome

Abstract: Nephrotic syndrome is not a single disease; rather, it is a term for numerous diseases and pathological types. Renal biopsy is of use in determining the diagnosis and prognosis, and for guiding treatment; however, the use of this intervention is limited due to its invasive nature. Abnormal kidney‑derived proteins in the urine of patients provide useful information regarding numerous pathological processes that occur in the kidneys, and may be considered a potential non‑invasive biomarker for kidney disease. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Several studies have aimed at identifying proteomic differences between these two nephropathies. In particular, it was shown that the calretinin and UBA52 levels were higher in FSGS [48,49], while the 39S ribosomal protein L17 was higher in MCD [48] (Table 2). Significantly higher levels of cathepsin B, cathepsin C, and annexin A3 were shown in cases of the collapsing variant of FSGS (characterized by glomerular collapse and a rapid loss of renal function) than in MCD, MN, and other FSGS variants [94].…”
Section: Minimal Change Disease and Focal Segmental Glomerulosclerosismentioning
confidence: 99%
“…Several studies have aimed at identifying proteomic differences between these two nephropathies. In particular, it was shown that the calretinin and UBA52 levels were higher in FSGS [48,49], while the 39S ribosomal protein L17 was higher in MCD [48] (Table 2). Significantly higher levels of cathepsin B, cathepsin C, and annexin A3 were shown in cases of the collapsing variant of FSGS (characterized by glomerular collapse and a rapid loss of renal function) than in MCD, MN, and other FSGS variants [94].…”
Section: Minimal Change Disease and Focal Segmental Glomerulosclerosismentioning
confidence: 99%
“…There is a number of studies comparing the pattern of urinary proteome of FSGS patients with the proteomic profiles of healthy controls and/or patients with other renal-diseases [5][6][7][8][9][10][11]. However, the past research have never confronted simultaneously the pattern of urinary proteome in FSGS patients with the proteomic profile of the normal status, IgA nephropathy (the second most common glomerulopathy worldwide) and the commonest subtypes of renal cancers i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is a number of studies comparing the pattern of urinary proteome of FSGS patients with the proteomic pro les of healthy controls and/or patients with other renal-diseases [5,6,7,8,9,10,11]. However, the past research have never confronted simultaneously the pattern of urinary proteome in FSGS patients with the proteomic pro le of the normal status, IgA nephropathy (the second most common glomerulopathy worldwide) and the commonest subtypes of renal cancers i.e.…”
Section: Introductionmentioning
confidence: 99%